RNA editing of AZIN1 induces the malignant progression of non-small-cell lung cancers - Xueda Hu; Jingyi Chen; Xiaoshun Shi; Fenglan Feng; King Wai Lau; Yaoqi Chen; Yusong Chen; Long Jiang; Fei Cui; Yalei Zhang; Xin Xu; Jin Li (Tumor Biology, 2017)
RNA editing is a widespread post-transcriptional mechanism that confers specific and reproducible nucleotide changes in selected RNA transcripts and plays a critical role in many human cancers. However, little is known about how RNA editing operates in non-small-cell lung cancers. Here, we measured the sequence and expression level of genes of antizyme inhibitor 1 and adenosine deaminase acting on RNA family in 30 non-small-cell lung cancer patient samples and 13 cell lines and revealed RNA editing S367G in antizyme inhibitor 1 is a high-frequent molecular events. We determined overexpression of antizyme inhibitor 1 with RNA editing, implying the oncogenic function of this alteration. We also detected the association of adenosine deaminase acting on RNA overexpression with RNA editing occurred in antizyme inhibitor 1 . Furthermore, the RNA editing could cause a cytoplasmic-to-nuclear translocation of antizyme inhibitor 1 protein and conferred the malignant phenotype of non-small-cell lung cancer cells. The in vivo experiment confirmed that this RNA editing confers higher capacity of tumor migration as well. In conclusion, antizyme inhibitor 1 RNA editing and its involvement in tumorigenesis of non-small-cell lung cancer pave a new way for potential clinical management of non-small-cell lung cancer.